Business information systems workshops : BIS 2015 international workshops, Poznań, Poland, June 24-26, 2015, Revised papers /: BIS 2015 international workshops, Poznań, Poland, June 24-26, 2015, Revised papers. (2015) - Unknown
No abstract available